Adaptation by the brown planthopper to resistant rice: A test of female-derived virulence and the role of yeast-like symbionts - Horgan, Finbarr G.; Peñalver Cruz, Ainara; Arida, Arriza; Ferrater, Jedeliza B.; Bernal, Carmencita C. (MDPI, 2021)
The adaptation by planthoppers to feed and develop on resistant rice is a challenge for pest management in Asia. We conducted a series of manipulative experiments with the brown planthopper (Nilaparvata lugens (Stål)) on the resistant rice variety IR62 (BPH3/BPH32 genes) to assess behavioral and bionomic changes in planthoppers exhibiting virulence adaptation. We also examined the potential role of yeast-like symbionts (YLS) in virulence adaptation by assessing progeny fitness (survival × reproduction) following controlled matings between virulent males or females and avirulent males or females, and by manipulating YLS densities in progeny through heat treatment. We found virulence-adapted planthoppers developed faster, grew larger, had adults that survived for longer, had female-biased progeny, and produced more eggs than non-selected planthoppers on the resistant variety. However, feeding capacity—as revealed through honeydew composition—remained inefficient on IR62, even after 20+ generations of exposure to the resistant host. Virulence was derived from both the male and female parents; however, females contributed more than males to progeny virulence. We found that YLS are essential for normal planthopper development and densities are highest in virulent nymphs feeding on the resistant host; however, we found only weak evidence that YLS densities contributed more to virulence. Virulence against IR62 in the brown planthopper, therefore, involves a complex of traits that encompass a series of behavioral, physiological, and genetic mechanisms, some of which are determined only by the female parent.